Pengaruh Program Makan Bergizi Gratis (MBG) terhadap Minat Belajar Siswa Sekolah Dasar - Amelia Bactiara Putri; Ulyatul Fahriyah; Ratna Yuliana Putri; Syifa' Muhtarom; Qonitatin Taibah; Putri Suci Ramadhani Sutiana; Rifki Afandi (Edukasi Elita : Jurnal Inovasi Pendidikan, 2026)
The low level of interest in learning for elementary school students remains a fundamental problem in the implementation of basic education in Indonesia. One factor suspected of contributing to this condition is the lack of optimal fulfillment of students' physical health and nutritional needs. The Free Nutritional Meal Program (MBG) is strategic government policy aimed at improving students' nutritional status as an effort support learning readiness and the quality of learning in schools. This study aims to analyze the effect of the Free Nutritional Meal Program on increasing interest in learning for elementary school students. The study used a quantitative approach with a quasi-experimental design using a one-group pretest-posttest model. The research subjects included elementary school students and teachers directly involved in the implementation of the MBG program. Data collection techniques were carried out through a learning interest questionnaire, observation of student learning activities, and structured interviews with teachers. The data obtained were analyzed using descriptive statistics and inferential statistics in the form of paired t-tests determine differences in learning interest before and after the program implementation. The results of the study are expected to show an increase in student interest learning after participating in the Free Nutritional Meal Program, which is characterized by increased attention, activeness, and motivation in the learning process. These findings are expected to provide empirical evidence that the Free Nutritional Meal Program not only contributes improving students' physical and health conditions, but also has positive impact on the psychological and academic aspects elementary school students.